Повалення чи нова розбудова мовно-культурної Вавилонської вежі в сучасній Україні - Бабич, Надія; Babych, Nadiia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Предметом аналізу у статті є особливості функціонування мови в сучасному українському суспільстві, загрози, спричинені тенденціями до соціально-етичної деградації суспільства, частими змінами вимог до дотримання закону про мови в Україні, дуалізмом поглядів на критерії повнофункціональності державної мови, її системи і мовленнєвої практики. The article offers insight into the solution of the global task of mankind to preserve modern universe that can be destroyed both by the fusion of languages and by struggle for the excessive purity of national language. The article argues that the processes of social and cultural selfidentification aimed at preserving and developing style, imagery, thought order and world perception of native speakers in their own national language, once in a while undergo influences caused by the global world tendencies. The people, who monitor the risks of language interferences, caused by the economic and political ambitions of some states that support the conception of unified language, strongly doubt the statements of sociologists and politicians that globalization will not ruin national cultures, traditions and languages. The article analyses the expedience of thought dualism which does not threaten to ruin the qualitative communicative features of the Ukrainian language and the national basis of its culture.
The Collapse or the Arrangement or the Babylonian Linguacultural Tower in Modern Ukraine
Keywords: культура; мова та історія народу; «сакрум»; «профанум»; мовна експансія; мовна система; мовлення; соціокультурна самоідентифікація; culture; national language; language and history of the people; «sacrum»; «profanum»; language expansion; speaking; selfidentification